(untitled) (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2025)
This article talks about the stages of the research of German proverbs, mentions the works of proverb scholars. The role of proverbs in the social life of Germans in the early periods, the importance of proverbs in society is revealed by examples of German proverbs